Utilization of waste high density polyethylene (HDPE) as coarse aggregate replacement and kaolin as filler in hot mix asphalt - Siti Nursuhana, Abu Bakar (2015)
Many researches and development of waste material as an alternative option to replace existing material in pavement design have been done nowadays. One of the common waste materials that used in research is High Density Polyethylene (HDPE). This research is about the utilization of waste HDPE as coarse aggregate replacement and Kaolin as filler in hot mix asphalt (I-IMA).The objectives of this study is to determine the optimum bitumen content, stiffness modulus and permanent deformation behavior of asphalt mixture. Waste I-[DPE will be replace the coarse aggregate (by weight) in five different percentages in range 2%, 4%, 6%, 8%, and 10% in flakes form. There are 3 samples for every percentage of HDPE. This research also used penetration grade bitumen of 80/100 and Kaolin as filler. Density and Voids analysis is carried out to find the optimum bitumen content. The determination of stiffness modulus of samples is done by Indirect Tensile Stiffness Modulus Test. Meanwhile the Repeated Load Axial Test (RLAT) is conducted in determines the permanent deformation of asphalt mixture. The results obtained from the experimental at laboratory, shows that the stiffness of asphalt is increase with 4% of HDPE usage. As for permanent deformation, it can be reduces the value of axial strain if the usage of T-TDPE is more than 10%. The finding also reveals that Kaolin plays important roles in increasing the stiffness and decreasing the axial strain of asphalt. This indicates that Kaolin give better performance than Portland cement as filler in asphalt mixture.